PENGARUH STRATEGI REACT DENGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DALAM MENINGKAT KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Yori Yupiter Juliansyah; Agus Susanta; Saleh Haji; Amelia Sari (LPPM Universitas Bina Bangsa, 2024)
The aim of the research is to determine the effect of the REACT strategy with LKPD on students' class XI Mathematics problem solving abilities at SMKN 5 Kepahiang. on the Opportunity material. This research is a quasi-experimental research whose population includes all class XI students at SMK Negeri 5 Kepahiang consisting of eight classes. The data collection technique in this research is an instrument test used to collect data including mathematical problem solving ability test questions. The researcher used a purposive sampling technique for sampling. The number of samples was determined using Taro Yamane's calculation formula so that 70 students were obtained consisting of 35 people in the control class and 35 people in the experimental class. Data collection in this research used documentation studies and tests. The data analysis technique uses the independent sample t-test, but before carrying out the t test, the data analysis requirements are tested, namely the normality test and homogeneity test. The results of the research show that the results of the normality and homogeneity tests show that all data is normally and homogeneously distributed, while the results of the hypothesis test show that the significance value is (0.00 < 0.05), which means that there is a positive and significant influence of the REACT learning strategy with LKPD on ability. Solving mathematics problems for students at SMK Negeri 5 Kepahiang on opportunity material